Assessment of Exoskeletons on Nurses' Quality of Work Life: A Pilot Study at Foch Hospital - Line Farah; Dorota Roll; Amrei Sorais; Alexandre Vallée (MDPI AG, 2023)
Background: The prevention of occupational risks is part of the quality of work life and it is a component that improves the physical work environment. The purpose of the present study was to investigate how to maintain posture and to reduce pain and fatigue for nurses, with an exoskeleton adapted to the work at hospital. Methods: The exoskeleton was used between 2022 to 2023 at Foch Hospital, France. Phase 1 consisted of the selection of the exoskeleton, and Phase 2 included the testing of the device by the nurses and a questionnaire to assess it. Results: The "active" ATLAS model from JAPET, ensuring lumbar protection, was selected because it corresponds to all the specification criteria to tackle the nurses' unmet need. Among the 14 healthcare professionals, 86% were women; the age of the nurses was between 23 years old and 58 years old. The global median satisfaction score of the nurses relative to the use of the exoskeleton was 6/10. The median impact of the exoskeleton on nurses' fatigue was 7/10. Conclusions: The implementation of the exoskeleton received global positive qualitative feedback from the nurses concerning the improvement of posture and the reduction in fatigue and pain.